EVALUASI PENYAJIAN LAPORAN KEUANGAN PEMERINTAH DAERAH KOTA SURABAYA BERDASARKAN PERATURAN PEMERINTAH NO 71 TAHUN 2010 - NISTA RINTIANI, WASIK Nista (Jurnal Akuntansi AKUNESA, 2014)
Government financial statements must conform PP No. 71 of 2010 on Government Accounting Standards. Application of these rules is still an obstacle in 184 local governments throughout Indonesia. This is proved by the small number of local governments that receive an unqualified opinion. The research objective was determine whether the PP No. 71 of 2010 has been applied to the Financial Statements of Surabaya City Government in 2013 because in that year, the City of Surabaya decreased audit opinion of WTP into WTP-DPP. The analytical method used is descriptive analysis method to collecting and interpreting the form of Financial Statements of Surabaya City Government in 2013. The results indicate that the City of Surabaya has yet fully implemented PP No. 71 of 2010 because they found a discrepancy with the PSAP 01 paragraph 51, PSAP 01 paragraph 78, PSAP 04 paragraphs 28 and 29, and PSAP 04 paragraph 20.Keywords : government accounting standards, the financial statements, local government